M. Hidiroglou, ΣΥΓΚΕΝΤΡΩΣΗ ΤΗΣ ΒΙΤΑΜΙΝΗΣ D3 ΣΕ ΟΡΙΣΜΕΝΟΥΣ ΙΣΤΟΥΣ ΤΟΥ ΠΡΟΒΑΤΟΥ ΜΕΤΑ ΕΝΔΟΜΥΪΚΗ ΕΓΧΥΣΗ Bitamin D3 levels in certain sheep tissues at various times after the intramuscular administration of vitamin D3. - Παππούς, Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Δεν διατίθεται περίληψη.